A Critique of Trade Disputes Settlement Mechanism in Nigeria: 1968 to 2004 - Anyim, Francis Chukwudike (University of Lagos, 2009)
Full texts attached
Keywords: Conflict Manifestation; Labour market research; Marxist Perspective; Process of Collective Bargaining; Strike and its effect

Status Ambiguity and Conflict in the Market - Tan, David (Emory University, 2009)
My main theoretical contention is that status hierarchies provide a source of guidance to firms for resolving disputes. A status hierarchy implies a system of deference rules among firms. When disputes arise, deference rules can provide a basis for shared expectations and protocols of conduct about how technical ambiguities should be resolved. In many contexts, technical merit is difficult to assess. However, deference rules can operate as social conventions to which firms default, helping to align potentially incompatible expectations. Within this general framework, my dissertation examines how competitors in the semiconductor industry manage uncertain and frequently overlapping patent rights. In practice, patent rights are highly imperfect legal instruments when it comes to demarcating each firm's contributions to innovation in the industry. Patent disputes arise because of the ambiguity this creates about how much of the collective market returns to innovation each firm is entitled to receive. Despite the prolific patenting and propensity for disputes, the industry has remarkably not ground to a halt from runaway litigation. Litigation events, while significant, are rare. I suggest that this degree of order is, at least partly, attributable to status processes. Status can operate as a stabilizing force in the market, helping to generate orderly competition in the face of disputes. To examine whether this is the case in the semiconductor industry, I theorize that disputes are less easily resolved when the parties involved face greater status ambiguity, i.e. are less clearly differentiated from one another in status. Under status ambiguity, deference rules lose the rule-like, universal quality that makes them persuasive in resolving disputes. This has two consequences. First, firms facing low status ambiguity are less likely to be involved in patent litigation than are firms facing high status ambiguity. Patent litigation events represent failures to resolve patent disputes out of court. Second, firms facing low status ambiguity increase their product line sizes more than do firms facing high status ambiguity. The threat of difficult-to-resolve patent disputes represents a cost that can deter firms from bringing products to market.
Keywords: Litigation; Patent; Semiconductor; Status

Milletlerarası Özel Hukukta kambiyo senetleri - Aygün, Mesut (Anadolu Üniversitesi, 2008)
Milletlerarası Özel Hukukta Kambiyo Senetleri başlığını taşıyan çalışmamız, üç bölümden oluşmaktadır. Bu konuyu seçmemizin başlıca nedeni, kambiyo senetleri alanında yapılan (veya yapılacak olan) yeknesaklaştırma çalışmalarının milletlerarası özel hukuk alanına etkilerini ortaya çıkarmaktır.Tezimizin Birinci Bölümünde, kambiyo senetleri (ticarî senetler) başlığı altında, öncelikle kanunlar ihtilâfı hukuku açısından önem arz eden kıymetli evrak ve kambiyo senetlerinin bazı konuları üzerinde genel hatlarıyla durulmuştur. Daha sonra, yabancılık unsuru, vasıflandırma, atıf, bağlama noktaları gibi kambiyo senetlerine ilişkin olarak ortaya çıkan kanunlar ihtilâfı hukukunun genel problemleri incelenmiştir. Son olarak, kambiyo senetlerine uygulanacak hukuka ilişkin olarak Cenevre Konvansiyonları sistemi ile Anglo-sakson hukuk sistemi genel olarak incelenmiştir.Tezimizin İkinci Bölümünde, milletlerarası özel hukuk düzenlemelerinde kambiyo senetleri başlığı altında, öncelikle kambiyo senetlerine ilişkin uyuşmazlıklarda milletlerarası yetki üzerinde durulmuştur. Bu konuya ilişkin olarak, Brüksel Konvansiyonu, Brüksel I Tüzüğü ve La Haye Konvansiyon taslağı gibi milletlerarası sözleşmeler incelenmiştir. Sonra, uygulanacak hukukun tespitinde faydalanılan taahhütlerin birliği ve taahhütlerin bağımsızlığı esasları ele alınmıştır. Anglo-sakson hukuk sisteminde kambiyo senetlerine ilişkin düzenlemeler incelendikten sonra, diğer sistem içinde kalan Cenevre konvansiyonları üzerinde durulmuştur.Tezimizin Üçüncü Bölümünde, Türk milletlerarası özel hukukunda kambiyo senetleri başlığı altında, yine öncelikle milletlerarası yetki konusu ele alınmıştır. Uygulanacak hukuk kısmında vasıflandırma üzerinde durulduktan sonra, önce poliçe ve bonolara uygulanacak hukuk, daha sonra çeke uygulanacak hukuk inceleme konusu yapılmıştır. Uygulanacak hukuka ilişkin incelemelerimizde önce ehliyet, şekil gibi kambiyo senedinin geçerlik şartlarına ilişkin konuları, sonra sırasıyla kambiyo taahhüdünün hükümlerine ve kambiyo taahhüdünün icrasına uygulanacak hukuk ile ilgili konular ele alınmıştır. Our study, under the title of Commercial Papers in Private International Law comprises three chapters. The main reason in choosing this subject is that reveal effects of unification works in the commercial papers on the field of private international law.In the first chapter of the thesis, under the title of commercial papers, first some subjects of negotiable instruments law and commercial papers which critically important for conflict of laws have been mentioned. Next, general matters of conflict of laws such as foreign element, classification, renvoi and connecting factors have been examined respectively. Lastly the system of Geneva Conventions and Anglo-sakson law system have been examined generally relating to applicable law.In the second chapter of the thesis, under the title of commercial papers in arrangements of private international law, first international jurisdiction dealing with the conflicts of commercial papers have been dwelled upon. International conventions such as Brussel Convention, Council Regulation (EC) No. 44/2001 and Draft of Hague Convention on Jurisdiction and Foreign Judgments in Civil and Commercial Matters regarding this subject have been examined. Next, the principle of combination of stipulations and the principle of independency of stipulations are used in determination of law applicable have been handled. After the arrangements of Anglo-sakson law were examined, the other system, Geneva Conventions? rules have been dwelled upon.In the third chapter of the thesis, under the title of commercial papers in Turkish private international law, first international jurisdiction has been handled. First the classification, then applicable law to bills of exchange and promissory note and applicable law to cheque has been examined. In this part, terms of validity of commercial papers such as capacity, form, applicable law to obligations arising out of a commercial paper and applicable law to subjects regarding discharge of a commercial paper have been handled respectively.
Keywords: Bill of exchange; Commercial law; Devletler özel hukuku; International adjective law; International private law; Kambiyo senetleri; Kanunlar ihtilafı; Kıymetli evrak; Laws conflict; Milletlerarası usul hukuku; Private international law; Ticaret hukuku; Uluslararası özel hukuk; Valuable paper

İcra ve İflas Hukuku açısından malvarlığı veya ticari işletmenin devri - Durman, Okay (İstanbul Üniversitesi, 2008)
Borçluların alacaklılarına zarar vermek kastıyla malvarlığını veya işletmesini devretmesi ile mücadeleye yönelik icra hukuku hükümlerinin incelendiği bu çalışmada üç ana bölüm yer almaktadır. İlk bölümde konunun kapsamını oluşturan malvarlığı, özel malvarlığı, işletme ve ticari işletme kavramları detaylı olarak tarif edilmektedir.İkinci bölümde maddi hukuk açısından, üçüncü bölümde değinilen İcra Hukuku hükümlerinin uygulanmasında önem taşıyan malvarlığı veya işletmenin devrinde devreden ve devralanın sorumluluğu açısından düzenleme getiren BK m. 179 hükmü, kaynak İsviçre ve Alman Hukukları'ndaki hükümler ile birlikte değerlendirilmektedir.Malvarlığı veya işletmesini alacaklılarına zarar vermek kastıyla devreden borçlularla mücadele olanaklarına sadece İcra Hukuku hükümlerinde yer verilmiş olması nedeniyle çalışmamızın asıl konusunu oluşturan üçüncü bölümde ise, İİK m. 280/III ve m. 44 uygulamasının olumlu ve olumsuz yanları, yargı kararları eşliğinde belirtilmektedir. There are three chapters in this work which deals with the regulations related to combating with the debtors who transfer their assets or businesses in order to harm their creditors. In the first chapter the asset, separate property, enterprise and businesses that are forming the scope of work are defined in details.In the second chapter, the Turkish Obligation Code Art. 179 that regulates the obligation of the debtors transfering their assets or businesses in order to harm their lenders is considered in light of the source law of Swiss and German regulations.For the reason that the only regulations for combating with the debtors who transfer their assets and businesses in order to harm their creditors are arranged within the Turkish Execution and Insolvency Code, in the third and the main chapter, the related articles of 280/III and 44 are considered in light of the Supreme Court decisions with their positive and negative effects.
Keywords: Bankruptcy law; Businesses; Commercial institutes; Contract of transfering; Devir sözleşmesi; Enforcement law; Malvarlığı; Property; Ticari işletmeler; Workplace transferring; İcra hukuku; İflas hukuku; İşletmeler; İşyeri devri

A onerosidade excessiva em contratos de engineering - Gil, Fabio Coutinho de Alcantara (Universidade de São Paulo, 2007)
O presente trabalho visa analisar em que medida a alteração das circunstâncias negociais que levem à situação de onerosidade excessiva prevista pelo Código Civil produz efeitos sobre a utilidade que as partes derivam dos contratos de engineering, considerados estes como contratos que têm por objeto o desenvolvimento de projetos industriais e de infraestrutura de grande porte. Situa esses contratos em seu contexto histórico e social, descrevendo seus principais elementos de distinção, especialmente a complexidade e risco das operações econômicas que lhes é subjacente e os qualifica como contratos socialmente típicos, sujeitos ao regime dos contratos de empreitada. A tese discute a adequação do tratamento jurisprudencial que vem sendo dado à onerosidade excessiva e descreve os esquemas negociais geralmente usados em tais contratos para fins de alocação de riscos. Finalmente, a tese discute a aplicação de modelos da Análise Econômica do Direito, como a Teoria dos Contratos Incompletos, como subsídio para a valoração de aplicabilidade das normas sobre onerosidade excessiva aos contratos de engineering e análise dos efeitos de sua aplicação sobre esses contratos.
Keywords: Complexity; Contrato administrativo; Contrato comercial; Contrato de risco; Contratos; Empreitada; Engenharia; Engineering agreements; Excessive onerosity; Law & economics; Risk allocation; Tecnologia; Theory of incomplete contracts

Kambiyo senetlerinde sebepsiz zenginleşme - Yasan, Mustafa (Marmara Üniversitesi, 2007)
Tezimizin konusu ?Kambiyo Senetlerinde Sebepsiz Zenginleşme?dir. Kambiyo senetlerinde sebepsiz zenginleşme müessesesi TTK m.644'te düzenlenmiştir. TTK m.644'e göre keşideci ve kabul etmiş muhatap, hamilin poliçedeki hakkını zamanaşımı ya da poliçedeki hakkı koruyucu işlemleri kaybetmesi sebebiyle poliçedeki borcu ödemek yükümlülüklerinden kurtulmuş olsa dahi sebepsiz zenginleşme hükümleri ile takip edilebilirler. TTK m.644'te düzenlenmiş olan kambiyo senetlerinde sebepsiz zenginleşme müessesesi kambiyo senedindeki asıl alacak ile genel hükümlerde yer alan sebepsiz zenginleşme talebinden bağımsız kendine özgü bir talebi içermektedir. TTK m.644 TTK m.730 gereği çekler hakkında da uygulanır. TTK m.690'da açık bir atıf olmamasına rağmen bonolara da uygulanabilmelidir. TTK m.644'ün uygulanabilmesi için hamilin zarara uğraması şarttır. Hamilin zararı iki sebebe dayanmalıdır. Bunlar, zamanaşımı ve hamilin poliçedeki hakkı koruyucu işlemlerin yerine getirilmemesidir. Zamanaşımı süreleri kambiyo senetlerinin türlerine ve kambiyo senetlerindeki alacaklı ve borçluların kimliklerine göre değişik süreler olarak TTK'da tespit edilmiştir. Hamilin poliçeyi muhataba kabul için arz etmemesi, ödenmek üzere ibraz etmemesi ya da gerektiğinde protesto keşidesinin gerçekleştirilmemesi poliçedeki hakkın kaybına yol açan hakkı koruyucu işlemler olarak kabul edilmektedir. Hamilin poliçedeki hakkını kaybetmesi neticesinde borçtan kurtulan borçlular zenginleşmiş olarak kabul edilirler. Kambiyo senetlerinde sebepsiz zenginleşme talebine dayanan dava mutlak ticari davadır. Görevli ve yetkili mahkeme Ticaret Hukuku, Borçlar Hukuku Usul Hukuku prensipleri birlikte değerlendirilerek tespit edilmelidir. Ve bu davaya uygulanacak zamanaşımı süresi hakkında doktrinde ve mahkeme kararlarındaki ihtilaf bu konudaki boşluğun kanun koyucu tarafından doldurularak giderilmelidir. [...] Tezimizin konusu ?Kambiyo Senetlerinde Sebepsiz Zenginleşme?dir. Kambiyo senetlerinde sebepsiz zenginleşme müessesesi TTK m.644'te düzenlenmiştir. TTK m.644'e göre keşideci ve kabul etmiş muhatap, hamilin poliçedeki hakkını zamanaşımı ya da poliçedeki hakkı koruyucu işlemleri kaybetmesi sebebiyle poliçedeki borcu ödemek yükümlülüklerinden kurtulmuş olsa dahi sebepsiz zenginleşme hükümleri ile takip edilebilirler. TTK m.644'te düzenlenmiş olan kambiyo senetlerinde sebepsiz zenginleşme müessesesi kambiyo senedindeki asıl alacak ile genel hükümlerde yer alan sebepsiz zenginleşme talebinden bağımsız kendine özgü bir talebi içermektedir. TTK m.644 TTK m.730 gereği çekler hakkında da uygulanır. TTK m.690'da açık bir atıf olmamasına rağmen bonolara da uygulanabilmelidir. TTK m.644'ün uygulanabilmesi için hamilin zarara uğraması şarttır. Hamilin zararı iki sebebe dayanmalıdır. Bunlar, zamanaşımı ve hamilin poliçedeki hakkı koruyucu işlemlerin yerine getirilmemesidir. Zamanaşımı süreleri kambiyo senetlerinin türlerine ve kambiyo senetlerindeki alacaklı ve borçluların kimliklerine göre değişik süreler olarak TTK'da tespit edilmiştir. Hamilin poliçeyi muhataba kabul için arz etmemesi, ödenmek üzere ibraz etmemesi ya da gerektiğinde protesto keşidesinin gerçekleştirilmemesi poliçedeki hakkın kaybına yol açan hakkı koruyucu işlemler olarak kabul edilmektedir. Hamilin poliçedeki hakkını kaybetmesi neticesinde borçtan kurtulan borçlular zenginleşmiş olarak kabul edilirler. Kambiyo senetlerinde sebepsiz zenginleşme talebine dayanan dava mutlak ticari davadır. Görevli ve yetkili mahkeme Ticaret Hukuku, Borçlar Hukuku Usul Hukuku prensipleri birlikte değerlendirilerek tespit edilmelidir. Ve bu davaya uygulanacak zamanaşımı süresi hakkında doktrinde ve mahkeme kararlarındaki ihtilaf bu konudaki boşluğun kanun koyucu tarafından doldurularak giderilmelidir. The title of this thesies is "Unjustified Enrichment in Commercial Papers". The concept of Unjustified Enrichment in Commercial Papers was regulated in TTK (Code of Turkish Commerce) article 644. According to TTK article 644, drawer and drawee who accepted the bill of exchange, can be fallowed by unjustified enrichment regulations even the holder looses the rights in commercial papers because of prescription and negligence for saving the rights in commercial papers. The concept of unjustified enrichment which was regulated in TTK article 644 consists of independent, exceptional, and sui generis demand against the general regulations in Code of Obligations and basic relations in the commercial papers. TTK article 644 can be applied for the cheques because of the special rule in TTK article 730. TTK article 644 should be able to be applied for the promissory notes eventhough there is not any special rule in TTK article 690. For TTK article 644?s ability to apply holder should have a damage. And this damage must have one of two limited reasons. These are prescription and the negligence for saving the rights in commercial papers. Prescription timings were determinated according to the changing of the commercial papers? kinds and the the holders? and debtors? identities in the Turkish Commercial Code. If holder does not supply the bills of exchange to the drawee for acceptance or if holder does not supply the commercial paper for payment or if required, protesting is not cared by the holder, the debt gets lost. The result of the holder?s loss of the rights in commercial papers is the enrichment of the debtors. The case which is related to unjustified enrichment is the perfect commercial case. Authorized and charged court should be determinated by focusing the principles in Commercial Law, Obligation Law and Procedure Law. And the conflict for the prescription timings in scientific and courting decisions should be solved by the law maker.

Essai sur le contrat de service en droit international privé - Cavalier, Georges A. (Université Jean Moulin Lyon 3, 2005)
Dans l'Union européenne, la notion de contrat de services a pris place au cœur du règlement des conflits de juridictions, et oriente la réflexion en matière de conflit de lois. Elle est en passe de devenir une catégorie du droit international privé, dans l'un des domaines en apparence épuisé et pourtant fondamental de cette discipline : celui du contrat. Cette évolution, confirmée par la récente proposition dite " directive Bolkestein ", ouvre des perspectives nouvelles et soulève toute une série de questions inédites, étudiées à la lumière des droits communautaire, français et néerlandais. C'est donc à l'analyse de cette notion en construction du contrat de services que la première partie de la thèse est consacrée. L'étude défend l'idée qu'en droit français, la définition de l'internationalité des services pose problème, car il n'est pas aussi facile d'identifier un passage de services au travers de la frontière qu'un mouvement de biens. Le droit communautaire recourt à une notion plutôt large : déplacement de l'une des deux parties au contrat et pas seulement des services transfrontaliers. Il semble mieux appréhender leur internationalité. La notion de contrat de services demeure donc autonome en droit international privé, y compris par rapport au – ou au sein même du – droit communautaire, puisqu'elle dépend du texte à interpréter. Les conventions de droit international privé attestent de l'affinité qu'entretient le contrat ayant pour objet des services portant sur un meuble, avec la qualification de vente. Au contraire, les contrats ayant pour objet des services portant sur un immeuble ressortiraient pleinement de la qualification de services. De cette notion en construction procède un régime du contrat de services en voie d'unification, objet de la deuxième partie de la thèse qui prend également quelques distances avec le droit positif. L'influence grandissante de la libre prestation de services communautaire, et ceci plus encore si la directive Bolkestein venait à être adoptée, pourrait bien élever la présomption de la " loi du prestataire " au rang de véritable principe : celui du pays d'origine. En définitive, la loi du prestataire ne se verrait court-circuitée que par l'autonomie de la volonté ou par les lois de police, notamment communautaires, auxquelles se cantonnent les mécanismes d'éviction. Quant au juge compétent, le Règlement Bruxelles I opère une simplification allant dans le sens de l'unification soutenue jusqu'alors, puisqu'il aide à l'interprétation des textes internes ou influence les législateurs nationaux. En effet, outre le juge du domicile du défendeur, le juge alternativement compétent est celui du lieu de livraison de la chose, objet des services, ou – si les services sont immatériels – celui du lieu de leur fourniture.
Keywords: Contrats; Contrats internationaux; Droit international privé; Droit international économique; Services

Le droit international privé face au contrat de vente cyberspatial - Guillemard, Sylvette (Université Laval ; Université Paris 2, 2003)
Depuis une vingtaine d’années, les humains utilisent la technique numérique pour nouer des relations à l’occasion desquelles peuvent se créer des liens juridiques. Parmi ceux-ci, le contrat de vente occupe une place importante. Traditionnellement, lorsque les contractants relèvent d’ordres juridiques différents, leurs rapports sont régis par le droit international privé. Celui-ci permet de déterminer d’une part quelle autorité pourra éventuellement être appelée à trancher les litiges et d’autre part quelles règles de droit seront appliquées pour y apporter une solution. Ce travail de recherche vise à vérifier si les règles de droit international privé régissant les ventes classiques peuvent être transposées aux contrats de vente cyberspatiaux. En d’autres termes, il s’agit d’en vérifier l’utilité et l’efficacité dans un monde dématérialisé et qui ignore les notions de frontières et de territorialité.
Keywords: Commerce électronique; Contrats (droit international privé); Réseaux d'ordinateurs; Vente (Droit international privé); Vente internationale

Elektronik sözleşmeler - Sağlam Atabarut, İpek (Marmara Üniversitesi, 2003)
Keywords: Avrupa Birliği; Commercial law; Contracts; Electronic signature; Electronics; Elektronik; Elektronik imza; European Union; International conventions; Internet; Signature; Sözleşmeler; Ticaret hukuku; Uluslararası sözleşmeler; İmza